Advancing Transformative Adaptation through Social Equity: Land, Water and Food Systems in the Global South - Fisher, Eleanor; Hellin, Jon; Kanui, Mary Ng’endo (2024)
An oft-repeated maxim is that those who are least responsible for climate change suffer the most from its consequences. The 1992 United Nation’s Framework Convention on Climate Change states that “[t]he Parties should protect the climate system for the benefit of present and future generations of humankind, on the basis of equity and in accordance with their common but differentiated responsibilities and respective capabilities (Article 3). The 2015 ‘Paris Climate Agreement’ repeats this, adding “in light of different national circumstances” (Article 2). If futures are to be sustainable, just and fair, then environmental sustainability research needs to address social equity even if this raises challenges for climate change adaptation.